The Impact of Foreign Trade Policies on Industrial Development in Syria - شحرور, سميع; نور الدين هرمز; علي أحمد (Latakia University Journal - Economic and Legal Sciences Series, 2024)
The research aimed to study the impact of foreign trade policies (exports and imports) on the development of the industrial sector (industrial domestic product) in Syria during the period 2000-2019. The statistical program Eviews.10 was relied upon to analyze the data, and the standard quantitative approach was used, including the unit root test, stationarity, Johanson cointegration test, VECM error correction model, and autoregressive (VAR) models. The statistical data and data available in the statistical collections were also relied upon, and the time frame for the research was determined during the period 2000-2019. The research results showed that there is an inverse effect of industrial exports and a positive effect of industrial imports on the industrial domestic product, and the industrial exports variable is considered the more influential of the two variables.